Highly efficient and reusable Ru-NaY catalyst for the base free oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic acid - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy (Catalysis Today, 2021)
Oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is an important reaction for the production of recyclable bio-based polymers. Herein, we report a series of Ru nanoparticles supported on NaY zeolites catalysts for the oxidation of HMF to FDCA. The catalysts were prepared by simple ion exchanged method. Among all the catalysts, the optimized 3 wt % Ru-NaY catalyst showed superior catalytic activity under base free conditions with a shorter period of reaction time. The conversion of HMF was 100 % with 94 % FDCA yield. This catalyst was reused for fourth cycles, with an insignificant decrease in the yield of FDCA. H2-chemisorption and HRTEM studies confirmed that high metal dispersion and small size of Ru nanoparticles play vital roles for the HMF oxidation. In addition, the acidic hydroxyl groups of the supercage as well as higher amount of metallic Ru° are also responsible for the high yield and productivity of FDCA.

Hydrodeoxygenation of guaiacol to cyclohexanol using noble metal-supported Ni-based perovskite-derived catalysts - Marimuthu, Prabu; Raja, Thirumalaiswamy; Vinu, Ravikrishnan (ChemCatChem, 2025)
This study focuses on the role of noble metal-doped Ni-based perovskites, specifically LaNiO3 and NiTiO3 catalysts in the hydrodeoxygenation (HDO) of guaiacol. The findings demonstrate that reduced Ru-LaNiO3 catalyst achieved superior performance with 100% guaiacol conversion and a 75% selectivity toward cyclohexanol, compared to reduced Ru-NiTiO3, which achieved only 43% conversion and 25% cyclohexanol selectivity under identical conditions (240 degrees C, 30 bar H2, and 4 h). High-resolution transmission electron microscopic (HR-TEM) analysis reveals that LaNiO3-supported catalysts exhibit better metal dispersion and smaller nickel nanoparticle sizes compared to NiTiO3-supported counterparts. X-ray photoelectron spectroscopy (XPS) analysis shows that the reduction of nickel and noble metals is more facile on LaNiO3. Additionally, the O 1s XPS profile for reduced Ru-LaNiO3 indicates a higher proportion of lattice oxygen (OLat similar to 79%) and a lower proportion of oxygen vacancies (OVac similar to 21%) compared to other catalyst systems. The optimized OLat/OVac ratio is shown to be critical for the effective HDO of guaiacol. In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) demonstrates a high HDO reaction rate using reduced Ru-LaNiO3 than reduced Ru-NiTiO3, with cyclohexanol formation attributed to the keto-enol tautomerization pathway. Overall, this study underscores the critical roles of oxygen vacancies, metal dispersion, and metal-metal oxide interactions in the HDO of guaiacol.
Keywords: Cyclohexanol; Guaiacol; Hydrodeoxygenation; In-situ DRIFT; Ni-based perovskites